حقــــــوق الإنسان بين الخصوصية الداخلية والمواثيق الدولية (العالمية) - ديدي, إبراهيم (University of Eloued جامعة الوادي, 2019)
المشرع الدستوري لم يكتف بإراد مجموعة من النصوص الدستورية التي تكفل حماية الحريات الأساسية وحقوق الإنسان بل ذهب إلى أبعد من ذلك بإنشاء آليات وهيئات دستورية ومنها المجلس الوطني لحقوق الإنسان الذي يتولى مهمة المراقبة والإنذار المبكر. كما أن القضاء الوطني في الجزائر هو الجهاز الأساسي المنوط به حماية الحقوق والحريات إذ له وحده سلطة تقييد الحريات وتوقيع العقوبات، ويمارس الرقابة على أعمال الإدارة وكذا سلطة الرقابة على دستورية القوانين التي يتولاها المجلس الدستوري. The constitutional legislator has not only wanted a set of constitutional provisions that guarantee the protection of fundamental freedoms and human rights, but went even further by establishing constitutional mechanisms and bodies, including the National Council for Human Rights, which has the task of monitoring and early warning. The national judiciary in Algeria is the primary organ entrusted with the protection of rights and freedoms. It alone has the authority to restrict freedoms and impose sanctions. It exercises control over the work of the administration, as well as the authority to monitoring the constitutionality of laws.
مجلد3، عدد2
Keywords: الحريات الأساسية ; عالمية حقوق الإنسان ; الرقابة على دستورية القوانين ; القضاء الوطني: Human rights; International Agreements; National judiciary; Constitutional laws